Ecological-edaphic and Socio-economic drivers of on-farm tree farming enterprises in Wakiso District, Central Uganda - Buyinza, Mukadasi (International Journal of Environmental & Agriculture Research, 2019)
The biophysical-edaphic and socio-economic factors do equally influence the on-farm tree farming in the smallholder farming systems. Naturally, neither of the factors do act in isolation, but they are interrelated. The study was carried out in Nsangi sub-county, Wakiso District, 2018. Using the stratified random sampling method based on landholding sizes, a sample of size of sixty households were selected and interviewed. The objectives of the study were to examine the influence of the bio-physical, edaphic and socio-cultural-economic factors onto the performance of the on-farm tree farming enterprise, and to evaluate the farmer's participation in on-farm tree farming activities. The results showed that both ecological-edaphic and socio-cultural-economic factors influence the performance of the tree volume, tree species diversity and tree stand density/ha. There is a negative correlation between size of landholding and farmer's interaction with the onfarm tree farming enterprises. Judging from the results of this study, there is a need for a policy review aimed at devising appropriate socio-cultural-economic and ecological-edaphic practices that promote on-farm tree farming programmes.
Keywords: On-farm tree farming enterprise, ecological-edaphic, socio-cultural-economic factors